The Effect Of Knowledge Management And Talent Management On Employee Performance - Hana Angelica Daniella Mantow; B. Medina Nilasari (Jurnal Manajemen, 2022)
The research objective is to see the impact of knowledge management and talent management on employee performance mediated by employee development. The sample of research is 225 employees who work in the field of information technology in the Jakarta area. Data analysis method using Structural Equation Model. The study showed that knowledge management and talent management have an impact on employee  performance, the employee development variable is proven to be a mediation between knowledge management and employee performance, but the employee development variable cannot mediate between talent management and employee performance. Companies should provide knowledge management such as providing company web facilities as a place where employees can share their knowledge, and also develop talent management with training and development programs that will improve employee performance.